Akuntabilitas Keuangan pada Organisasi Pengelola Zakat (Opz) di Daerah Istimewa Yogyakarta - Rifqi Muhammad (Journal of Accounting and Investment, 2006)
This research examines the financial accountability in Amil Zakah Institution (OPZ). As a non-profit organization that receive fund from donors (muzakki), manage and distribute their fund to the mustahiq (the group of people who have right in receiving zakah fund), OPZ should give financial statement regularly as a form of their responsibility to the society, especially to muzakkies. The samples used in this study are 8 amil zakah institutions in Yogyakarta. The results of this research are as follows: first, all of the institutions have made financial accountability but in different models based on the characteristics of the institutions. Second, almost of the institutions observed do not have a good accounting system and internal control. Third, all of the observed institutions have the same problem of not having accounting standard in processing financial accountability and lack of quality of human resources in managing financial division.